Development of tunneling detection model: a new corporate performance improvement - Sari, Ratna Candra; Fatimah, P.L. Rika; Djajadikerta, Hadrian Geri (Penerbit Universiti Kebangsaan Malaysia, 2016)
Tunneling through related party transactions is one of the most challenging aspects in corporate governance. In addition, the impact of tunneling activities may affect to corporate governance’s performance in most of Asian countries. Yet, studies on the effectiveness of corporate governance in relation to tunneling are still limited and the results have been inconclusive. This study tries to develop a detection model to distinguish related party transactions that can be categorised as tunneling activities. Furthermore, this study also examines whether corporate governance mechanisms can explain the tunneling activities. The main findings of this study suggest that companies, in Indonesian listed companies, with concentrated ownerships have a greater tendency to conduct tunneling transactions compared to companies with dispersed ownerships, and the overall corporate governance mechanisms implemented by the companies could not be used as predictors for tunneling behaviour.